US–CHINA STRATEGIC RIVALRY IN THE SOUTH CHINESE SEA: THE IMPACT OF CHINA’S ISLAND MILITARIZATION ON ESCALATIONS RISK (2013–PRESENT) - Shalyra Andini Tantra (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
This paper discusses the competition between the United States and China in the South China Sea, focusing on China's construction and use of artificial islands for military purposes and how it could trigger a larger conflict from 2013 until now. Using the security dilemma theory as an analytical perspective, this paper examines how actions initially intended to protect itself have instead exacerbated tensions in the region. Building runways, radars and missile systems on artificial islands in the Spratly Islands to expand its military influence while the United States sends military ships and aircraft to the region as a sign that it will not allow sea lanes to be closed or controlled by China. Based on various academic papers, research reports, and official government statements, this paper argues that the increasing military activity of both countries in this narrow and contested region increases the likelihood of misunderstandings leading to accidental clashes. While some argue that military buildup can actually prevent war by making the opposing side think twice, this paper concludes that weak communication channels between the two countries and the high level of conflicting interests make the South China Sea one of the most dangerous flashpoints in international relations today.